Manajemen Kesehatan Lansia Melalui Edukasi Senam Prolanis Terhadap Peningkatan Pengetahuan Lansia Dengan Rheumatoid Arthritis - Putri, Gebi Monika Yolanda; Badriansyah, Badriansyah; Oktaviani , Intan; Istiqoma , Siti; Yose, Yose; Hilmiffah , Destyenie; Royani , Tutik; Diana , Pela; Khotijah , Eri; Daryani, Lismah; Marlina , Yenny; Pebriani , Emi (Utami Publisher, 2024)
Problems that often occur in the elderly include arthritis and bone disorders because they interfere with vital activities for the elderly. To overcome this, it is necessary to provide information or knowledge in the form of education. One form of education that can be provided is prolanis exercises. This study aims to obtain an overview of the increase in knowledge of elderly people with rheumatoid arthritis after receiving knowledge about prolanis exercises. The research design used a case study approach in 2 groups of elderly people suffering from rheumatoid arthritis, each group consisting of 3 people. The results of the health education research were said to be successful because there was an increase in knowledge, in group 1 the elderly before receiving education was 47% after receiving education an increase of 73% and in group 2 the elderly before receiving education was 50% after receiving education 80%. There was an influence of health education on changes in the level of knowledge in a group of rheumatoid arthritis sufferers after being given prolanis exercise education. It is hoped that health education about prolanis exercises can increase the knowledge of rheumatoid arthritis sufferers and can be used as an alternative to reduce pain apart from taking pharmacological drugs.